Comparison of antimicrobial effect of Ziziphora tenuior, Dracocephalum moldavica, Ferula gummosa, and Prangos ferulacea essential oil with chlorhexidine on Enterococcus faecalis: An in vitro study - Bahareh Nazemisalman; Surena Vahabi; Ali Yazdinejad; Fatemeh Haghghi; Mahsa Shabbuii Jam; Fatemeh Heydari (Wolters Kluwer Medknow Publications, 2018)
Background: Different irrigating solutions with high antimicrobial activity have been introduced for cleaning of the root canal system. However, effects of Prangos ferulacea (PF), Ziziphora tenuior (ZT), Dracocephalum moldavica (DM), and Ferula gummosa (FG) on oral and dental pathogens have not been extensively evaluated due to their optimal biocompatibility and insignificant side effects. The aim of this study was to evaluate the antibacterial effects of essential oils of mentioned plants on Enterococcus faecalis. Materials and Methods: In this in vitro study the plants were collected from Zanjan Province, Iran. Analysis of the essential oil was carried out by gas chromatography/mass chromatography. Micro-broth dilution and disc diffusion methods were used for assessment of the antimicrobial activity, and minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated. Results: All the four essential oils had antibacterial effects on E. faecalis, and ZT had the greatest antibacterial activity. Assessment of the mean diameter of the growth inhibition zone showed higher antibacterial activity of PF and ZT than that of chlorhexidine. The MIC and MBC of ZT showed that the antimicrobial activity of ZT against E. faecalis was greater than that of other plants evaluated in this study. Conclusion: The results of this study indicated significant antibacterial effects of the mentioned plants on E. faecalis. The greatest antimicrobial activity belonged to ZT. The current study suggests extraction of effective compounds in these medicinal plants to use them in the clinical setting.